Chemical speciation distribution, desorption characteristics, and quantitative adsorption mechanisms of cadmium/lead ions adsorbed on biochars - Li Liu; Shisuo Fan; Zixin Wang; Jingjing Hu (Arabian Journal of Chemistry, 2024)
The adsorption characteristics of Cd2+ and Pb2+ with biochars have been widely reported. However, the desorption characteristics, chemical speciation, and stability of Cd2+ and Pb2+ adsorbed on biochars remain unclear. In this work, rice straw biochars were obtained at different pyrolysis temperatures (RSBC300, RSBC500, RSBC700). The chemical speciation and desorption characteristics of Cd- and Pb-loaded on biochars were investigated through Tessier sequential extraction and different desorption agents, and possible quantitative mechanisms of metal-laden biochars were revealed. Pyrolysis temperature influenced the properties of biochars obviously, including surface morphology, element and mineral composition, and carbon structure defects. RSBC700 and RSBC500 exhibited the highest adsorption capacity toward Cd2+ and Pb2+, respectively. The majority of adsorbed metal ions on rice straw biochars are distributed in the carbonate fraction and the exchangeable fraction. Cd and Pb in all metal-loaded biochars showed a high risk with risk assessment code values larger than 50 %. HCl and EDTA-2Na could desorb most of the Cd2+ from the Cd-laden biochars, and desorb most of Pb2+ from high-temperature Pb-laden biochars. Precipitation with minerals (Qpre, 52.77 %–82.37 %) and interaction with π-electrons (Qπ, 16.57 %–30.26 %) were the main Cd2+ adsorption mechanisms for all biochars, whereas precipitation with minerals (Qpre, 18.82 %–58.71 %) and ion exchange (Qexc, 19.18 %–48.81 %) were the main removal mechanisms for Pb2+. Therefore, Cd2+ and Pb2+ adsorbed on biochars were not stable and easily released to the environment, which showed a high potential environmental risk.